Prolonged migraine aura resembling ischemic stroke following CoronaVac vaccination: an extended case series - Suwanwela, Nijasri C.; Kijpaisalratana, Naruchorn; Tepmongkol, Supatporn; Rattanawong, Wanakorn; Vorasayan, Pongpat; Charnnarong, Chutibhorn; Tantivattana, Jarturon; Roongruang, Sirigunya; Ongphichetmetha, Tatchaporn; Panjasriprakarn, Poonnakarn; Chutinet, Aurauma; Akarathanawat, Wasan; et al. (My University, 2022)
Background: After the initiation of the COVID-19 vaccination program in Thailand, thousands of patients have experienced unusual focal neurological symptoms. We report 8 patients with focal neurological symptoms after receiving inactivated virus vaccine, CoronaVac. Case series: Patients were aged 24–48 years and 75% were female. Acute onset of focal neurological symptoms occurred within the first 24 h after vaccination in 75% and between 1-7d in 25%. All presented with lateralized sensory deficits, motor deficits, or both, of 2–14 day duration. Migraine headache occurred in half of the patients. Magnetic resonance imaging of the brain during and after the attacks did not demonstrate any abnormalities suggesting ischemic stroke. All patients showed moderately large regions of hypoperfusion and concurrent smaller regions of hyperperfusion on SPECT imaging while symptomatic. None developed permanent deficits or structural brain injury. Discussions: Here, we present a case series of transient focal neurological syndrome following Coronavac vaccination. The characteristic sensory symptoms, history of migraine, female predominant, and abnormal functional brain imaging without structural changes suggest migraine aura as pathophysiology. We propose that pain related to vaccine injection, component of vaccine, such as aluminum, or inflammation related to vaccination might trigger migraine aura in susceptible patients.
Keywords: CoronaVac vaccine; Cortical spreading depression; COVID-19; Neurological deficit; Sinovac